Communication Interoperability between EV Charging Infrastructure and Grid - Ju, Seung-Hwan; Lee, Il-Ho; Song, Sang-Hoon; Seo, Hee-Suk (International Journal of Engineering and Technology, 2018)
Background/Objectives: Although ISO/IEC 15118 deals with data communication between an electric vehicle and a charging station, communication with the extern is essential for establishing a system for V2G service.Methods/Statistical analysis: Data mapping table is created by comparing and analyzing the data model of electric car charging infrastructure and the data model of grid network communication.To integrate into IEC 61850 communications, the electric vehicle data model is expressed as SCL.The gateway links data between the electric car and the power network.Communication interoperability is an important issue to share the syntax of data.Findings: This research selects messages that communicate with the power grid among the use cases of the EV charging infrastructure. It is important to maintain the syntax for communication interoperability between two domains. The gateway we built ensures interoperability between the charging infrastructure of the EV and the grid. We verify the information of EV charging infrastructure in power grid through communication link between ISO/IEC 15118 electric vehicle model and IEC 61850 standard MMS protocol.Improvements/Applications: This is demonstrated so that the communication data is linked with the micro-grid system. This could be used as an element technology in other distributed power in the future.Â Â
Keywords: Electric Vehicle; Communication Integration; EV Charging Infrastructure; SmartGrid; Interoperability